A Preliminary Survey of Weed Species on Two Rural Lakes in Kepala Batas, Pulau Pinang - Ismail, Azma Hanim; Mansor, Mashhor; Wan Omar, Wan Maznah (2004)
A survey of the distribution of weeds was carried out in two rural lakes in Bumbung Lima, Kepala Batas, Pulau Pinang. A total of 36 taxa representing to 22 families have so far been identified. The results showed that Gramineae notably Phragmites communis was dominant at the sampling station followed by Scirpus grossus and Polygonum barbatum. The vegetation of weed species in the area was studied primarily towards identifying of plant species present and their distribution. The objectives of this study are to describe the species composition and diversity of weed species around the lakes.